Ionospheric Alfvén resonator observed at low‐latitude ground station, Muroto. Issue 7 (12th July 2017) - Nosé, M.; Uyeshima, M.; Kawai, J.; Hase, H.
Abstract: The ionospheric Alfvén resonator (IAR) is found in a dynamic power spectrum of the geomagnetic field variations as spectral resonance structures in the frequency range of 0.1–10 Hz. To date, observations of IAR at low latitude have only been made by a few studies employing a single ground observatory and are not sufficient enough to reveal its general characteristics. We analyze data measured with an induction magnetometer installed at Muroto, Japan (24.40° geomagnetic latitude) for the period from 28 December 2013 to 13 August 2016. A statistical analysis reveals that the occurrence probability of the low‐latitude IAR is (1) dominant during nighttime with a gradual increase from dusk to midnight and a broad maximum at 00–05 LT followed by a sudden decrease at dawn, (2) slightly higher during May through September, and (3) independent of the Kp index for Kp ≤ 5. We also find that (4) the frequency separation between the harmonics (Δ f ) of the low‐latitude IAR is 0.1–0.5 Hz with a peak at 0.2–0.275 Hz. These observational results are compared with the model calculation results along with previous studies about possible energy sources. It is found that the global thunderstorm activity is a likely source for IAR at Muroto; that is, it produces electromagnetic disturbances that are converted into the Alfvén waves and that are then trapped in the ionospheric cavity bounded by the conductive E layer and a steep gradient of Alfvén velocity above the F 2 layer to form the resonant Alfvén waves. Key Points: The ionospheric Alfvén resonator (IAR) observed at a low‐latitude station, Muroto (24.40° geomagnetic latitude), is statistically studied IAR occurs frequently during nighttime and from May to September with frequency separation between the harmonics of 0.2–0.275 Hz A likely source for IAR at Muroto is the global thunderstorm activity